Philological Analysis of Tafsiriyah Translations in Javanese Qur'an Manuscripts from a Nusantara Perspective - Febriyanti, Fitri; Alawy, Muhammad Syihabudin (Jurnal Lektur Keagamaan, 2025)
This study explores the translation methodologies of three Javanese Qur'an manuscripts: Serat Alpatékah, Kuran Jawi and Kitab Kuran. These manuscripts primarily employ tafsiriyah translation, a method that, while effective linguistically, often overlooks sociocultural aspects that can influence public acceptance of the translation. To address this gap, this research investigates how translation strategies in these regional language Qur'an manuscripts account for the socio-cultural nuances inherent in each translator's local context. The study adopts a descriptive-philological approach, utilizing Javanese words, phrases, and sentences—specifically from the translation of Surah Al-Baqarah—as its primary data. Data were collected through interviews, observation, and documentation. The findings reveal that both formal and dynamic equivalence are used to varying degrees within the tafsiriyah translation method, particularly evident in the absorption of Arabic elements into Javanese and in word equivalence. Furthermore, the tafsiriyah translation method demonstrates a greater prevalence of semantic translation strategies compared to structural strategies. Future research should also consider Javanese Qur'an manuscripts written in Javanese script, as they offer valuable insights into the cultural and historical variations embedded within Javanese language varieties.